2022
DOI: 10.3389/fradi.2022.810731
|View full text |Cite
|
Sign up to set email alerts
|

The value of AI in the Diagnosis, Treatment, and Prognosis of Malignant Lung Cancer

Abstract: Malignant tumors is a serious public health threat. Among them, lung cancer, which has the highest fatality rate globally, has significantly endangered human health. With the development of artificial intelligence (AI) and its integration with medicine, AI research in malignant lung tumors has become critical. This article reviews the value of CAD, computer neural network deep learning, radiomics, molecular biomarkers, and digital pathology for the diagnosis, treatment, and prognosis of malignant lung tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
(83 reference statements)
2
0
0
Order By: Relevance
“…Therefore, the results have shown that artificial intelligence (that is, deep learning, which is its subset) is a usable tool in the diagnosis of these diseases. The findings are in parallel with the findings of other studies in the literature ( 22 , 25 , 26 , 51 , 57 ), which suggest that deep learning networks are successful in diagnosing diseases such as COVID-19 and Viral Pneumonia. Therefore, the first of the research questions, “Can deep learning networks (ResNet101, AlexNet, GoogLeNet and Xception) be successful in detecting COVID, Viral Pneumonia and healthy X-ray images?” was answered positively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the results have shown that artificial intelligence (that is, deep learning, which is its subset) is a usable tool in the diagnosis of these diseases. The findings are in parallel with the findings of other studies in the literature ( 22 , 25 , 26 , 51 , 57 ), which suggest that deep learning networks are successful in diagnosing diseases such as COVID-19 and Viral Pneumonia. Therefore, the first of the research questions, “Can deep learning networks (ResNet101, AlexNet, GoogLeNet and Xception) be successful in detecting COVID, Viral Pneumonia and healthy X-ray images?” was answered positively.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the results have shown that artificial intelligence (that is, deep learning, which is its subset) is a usable tool in the diagnosis of these diseases. The findings are in parallel with the findings of other studies in the literature (22,25,26,51,57) (22,25,58) for the detection of COVID-19, but no comparison has been made for the detection of different diseases using CNNs. In some studies [e.g., (28)], there has been a call to examine lung diseases such as pneumonia, lung cancer and COVID-19 together for future studies.…”
Section: Discussionsupporting
confidence: 81%